Efektivitas Mediasi Sebagai Alternatif Penyelesaian Tindak Pidana Dalam Perspektif Restorative Justice - Magdhalena Tasik Todingrara (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Restorative justice or restorative justice, is an approach that emphasizes restoring losses experienced by victims, reintegrating perpetrators into society, and repairing social relationships damaged by criminal acts. In contrast to the retributive approach which focuses on punishment as retribution for legal violations, this research aims to analyze the concept of mediation as an alternative for resolving criminal acts from a restorative justice perspective and the effectiveness of mediation in reducing the burden on the courts and increasing the efficiency of the criminal justice system. This research is a type of normative legal research that uses a conceptual approach. The data source used in this research is secondary data. The results of this research are that mediation as an alternative for resolving criminal acts from a restorative justice perspective has great potential to create more substantive and sustainable justice. Mediation is an effective tool for reducing the burden on courts and increasing the efficiency of the criminal justice system. By providing a faster, more cost-effective and flexible dispute resolution mechanism, mediation not only helps reduce the backlog of cases in court, but also creates more satisfactory solutions for victims and perpetrators.